Europe's resilience to threats gets better. (Research'eu results magazine)
Alongside benefits, globalisation has also increased the reach of threats, both accidental and malicious. Europe must now be more ready than ever to combat threats of a chemical, biological, radiological, nuclear or explosives (CBRNE) nature.